2018
DOI: 10.1177/2333721418801027
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Environmental Determinants of Provider Continuity Among Urban Older Adults With Heart Failure: A Retrospective Cohort Study

Abstract: Objective: Continuity in patient–provider relationships is important to providing high-quality care for older adults with chronic conditions. We investigated individual and environmental determinants of provider continuity for office-based physician visits among urban older adults with heart failure. Method: We linked Medicare claims with data on neighborhood characteristics for a retrospective cohort of community-dwelling Medicare beneficiaries with heart failure in New York City (N = 50,475). Results: Mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Our findings demonstrated that multimorbidity, using the PCG counts approach, is significantly but weakly positively associated with COC. This is partially in line with earlier studies, which applied the approaches of chronic condition counts or morbidity indices ( Chung et al, 2016 ; Dreiher et al, 2012 ; Kohnke & Zielinski, 2017 ; Ryvicker & Russell, 2018 ; Sharma et al, 2009 ). Stemming from existing literature on multimorbidity and fragmentation of care ( Pham, Schrag, O'Malley, Wu, & Bach, 2007 ; Sheaff et al, 2015 ), one may assume that higher multimorbidity is associated with lower COC.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings demonstrated that multimorbidity, using the PCG counts approach, is significantly but weakly positively associated with COC. This is partially in line with earlier studies, which applied the approaches of chronic condition counts or morbidity indices ( Chung et al, 2016 ; Dreiher et al, 2012 ; Kohnke & Zielinski, 2017 ; Ryvicker & Russell, 2018 ; Sharma et al, 2009 ). Stemming from existing literature on multimorbidity and fragmentation of care ( Pham, Schrag, O'Malley, Wu, & Bach, 2007 ; Sheaff et al, 2015 ), one may assume that higher multimorbidity is associated with lower COC.…”
Section: Discussionsupporting
confidence: 90%
“…In these data African American and Hispanic patients were referred from a hospital more often than non‐Hispanic whites. African American and Hispanic patients are less likely to have a regular care source . Referrals from hospital physicians caring for acutely ill PWD, who may be unable to consult with a physician familiar with the patient's condition and trajectory, may lead to premature hospice referrals among these groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the average ambulatory COCI values were as follows: oncology specialists (0.71) and primary care physicians (0.54). In relevant empirical studies on chronic diseases in the past, the mean COCI of outpatient care provided by physicians was 0.66 for asthma patients [57], 0.55–0.79 for patients with chronic obstructive pulmonary disease [57,58,59], 0.33–0.55 for patients with chronic heart failure [60], 0.50–0.71 for patients with diabetes [58], and 0.74 for patients with hypertension [57]. Continuity of care is related to disease characteristics; therefore, patients requiring long-term treatment and follow-up tend to have better ambulatory continuity of care [59].…”
Section: Discussionmentioning
confidence: 99%